Handbook of bioelectronics : directly interfacing electronics and biological systems - Carrara, Sandro; Iniewski, Krzysztof, 1960- (Cambridge University Press, 2015)
This wide-ranging summary of bioelectronics provides the state of the art in electronics integrated and interfaced with biological systems in one book. It is a perfect reference for those involved in developing future distributed diagnostic devices, from smart bio-phones that will monitor our health status to new electronic devices serving our bodies and embedded in our clothes or under our skin. You will learn how to design complex circuits whilst cutting design time and cost and avoiding mistakes, misunderstandings, and pitfalls. An exhaustive set of recently developed devices is also covered, providing the implementation details and inspiration for innovating new solutions and devices. It includes real-world examples, step-by-step design details, and hints and tips. --